Question
Asked Dec 3, 2019
20 views

Derive the formula by using integration by parts on the left-hand side. (Assume n > 0.)

 

X-1ex dx
xnex dx xnex
u =
dx
dv
dx
du
help_outline

Image Transcriptionclose

X-1ex dx xnex dx xnex u = dx dv dx du

fullscreen
check_circle

Expert Answer

Step 1

Given:

help_outline

Image Transcriptionclose

e dx

fullscreen
Step 2

We will solve this by integration by part:

help_outline

Image Transcriptionclose

Jucdh= n-jrdu where u is the first function and v is the second function by ILATE So,by ILATE u = x"and v = e* d fare d=x*e¢ -fe 4(x*) Jre'dx=x*e° =fe'm* =x"e - e*.

fullscreen
Step 3

Compare the equation [2] w...

help_outline

Image Transcriptionclose

u = x d dv dx d du x*)= nx1

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Calculus

Integration